Characterization of the Genitourinary Microbiome of 1,165 Middle-Aged and Elderly Healthy Individuals - Qin, Junjie; Shi, Xulian; Xu, Junming; Yuan, Simin; Zheng, Bo; Zhang, Enpu; Huang, Guixiao; Li, Guo; Jiang, Ganggang; Gao, Shan; Tian, Cheng; Guo, Ruochun; et al. (Frontiers in Microbiology, 2021)
Accumulated evidence shows complex microbial communities resides in the healthy human urinary tract and can change in urologic disorders. However, there lacks a comprehensive profiling of the urinary microbiota in healthy cohort. Here, we performed 16S rRNA gene sequencing of midstream urine specimens from 1,172 middle-aged and elderly healthy individuals. The core microbiota included 6 dominant genera (mean relative abundance >5%) including Prevotella, Streptococcus, Lactobacillus, Gardnerella, Escherichia-Shigella and Veillonella, and 131 low-abundance genera (0.01-5%), displaying a distinct microbiome profiles to that of host-matched gut microbiota. The composition and diversity of genitourinary microbiome were distinct between genders, and may fluctuate with ages. Several urotypes were identified by the stratification of microbiome profiles, which were mainly dominated by the 6 most predominant genera. The prevalence of urotypes was disparate between genders, and the male sample additionally harbored other urotypes dominated by Acinetobacter, Corynebacterium, Staphylococcus or Sphingomonas. Peptoniphilus, Ezakiella and Porphyromonas were co-occurred and co-abundant, and they may play crucial roles as keystone genera and be associated with increased microbial diversity. Our results delineated the microbial structure and diversity landscape of the genitourinary microbiome in healthy middle-aged and elderly adults, and provided insights into the influence of gender and age to it.